Sybil attack detection in VANET using neighbouring vehicles. (5th December 2014) - Grover, J.; Laxmi, V.; Gaur, M.S.
In vehicular ad hoc networks (VANETs), vehicles are enabled to exchange information to detect and mitigate critical situations. VANETs are vulnerable to many security threats. One severe attack is Sybil attack, in which a malicious node forges large number of fake identities in order to disrupt the proper functioning of VANET applications. Fake information reported by a single malicious vehicle may not be highly convincing because most of the VANET applications require several vehicles to reinforce a particular information before accepting as a truth. A Sybil attacker pretends multiple vehicles in order to reinforce false messages. Proposed methodology exploits the characteristics of Sybil nodes as the neighbours of fake identities (originated from a malicious node) share significant common neighbouring nodes. Motivation behind the design of proposed approach is to locate Sybil nodes quickly without using secret information exchange and special hardware support. We evaluate our proposed approach on the realistic traffic scenario.